Prevention of treatment related adverse effects in cystic fibrosis - Jain, Kamini (2018)
Cystic fibrosis (CF) is one of the commonest life-limiting genetic disorders in the Caucasian population. Management involves frequent administration of antibiotics including aminoglycosides. With improving survival, it is time to focus on various age-related and treatment-associated adverse influences. The objective of this research was to evaluate renal function in CF, determine the effects of cumulative antibiotic exposure and to identify ways to reduce associated comorbidity. A cross-sectional study showed that a small number of adults and children with CF had low glomerular filtration rate (GFR), and there was no association between GFR and cumulative antibiotic exposure. An above normal GFR was identified in one in four children with CF. Estimated GFR calculated by creatinine-based equations did not accurately predict the GFR measured by the gold standard 51Cr-EDTA (51chromium-ethylenediamine tetraacetic Acid). Pure tone audiograms identified a raised hearing threshold in one in four people with CF, which did not correlate with increasing aminoglycoside exposure. A randomised controlled study established that there is no difference in the pharmacokinetics of tobramycin when administered intravenously in the morning or evening. A Cochrane systematic review concluded that there was insufficient evidence to support a routine use of bronchoalveolar lavage in the management of pulmonary infections with Pseudomonas aeruginosa in children with CF below 5 years old. CF gene (Cystic Fibrosis Transmembrane Conductance Regulator, CFTR) is expressed in pig kidneys. Histological and molecular experiments established that there is no difference between the newborn pigs with genotypes CFTR -/- (knockout) and CFTR +/- (heterozygous) or CFTR +/+ (wild-type) pig kidneys in the renal morphology and in the expression of various renal endocytic receptor proteins. The vascular haemodynamic parameter, augmentation index ascertained in a small group of children with CF suggests a possibility that the vascular age may be advanced in people with CF right from their childhood. In summary, these studies have established a low prevalence of renal disease in CF and a lack of association between cumulative antibiotic exposure and GFR. Further research is needed to evaluate the natural history of high GFR in paediatric CF population. Kidneys from pig model of CF may provide an alternative model to investigate the renal disease in CF.